1998
DOI: 10.1175/1520-0477(1998)079<2457:sbiipf>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Satellite–Based Insights into Precipitation Formation Processes in Continental and Maritime Convective Clouds

Abstract: Multispectral analyses of satellite images are used to calculate the evolution of the effective radius of convective cloud particles with temperature, and to infer from that information about precipitation forming processes in the clouds. Different microphysical processes are identified at different heights. From cloud base to top, the microphysical classification includes zones of diffusional droplet growth, coalescence droplet growth, rainout, mixed-phase precipitation, and glaciation. Not all zones need app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
520
6
10

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 561 publications
(569 citation statements)
references
References 20 publications
33
520
6
10
Order By: Relevance
“…Effective radius is the cloud droplet size distribution parameter, which is observable by satellites. It has already been observed by satellite that re decreased below the precipitation threshold of re=14 gtm in clouds infected by smoke from burning vegetation in the Amazon [Kaufman and Fraser, 1997] and Indonesia [RosenfeM and Lensky, 1998]. However, these studies did not provide direct evidence showing how the smoke actually suppresses precipitation, such as presented in the current study.…”
Section: Introductioncontrasting
confidence: 73%
“…Effective radius is the cloud droplet size distribution parameter, which is observable by satellites. It has already been observed by satellite that re decreased below the precipitation threshold of re=14 gtm in clouds infected by smoke from burning vegetation in the Amazon [Kaufman and Fraser, 1997] and Indonesia [RosenfeM and Lensky, 1998]. However, these studies did not provide direct evidence showing how the smoke actually suppresses precipitation, such as presented in the current study.…”
Section: Introductioncontrasting
confidence: 73%
“…5). This leads to profound differences in the precipitation processes, along the lines inferred by satellite observations (6,7,20). The shift of onset of precipitation to large H under smoky conditions leads to formation of large ice hydrometeors that were reported on the ground as large hail (up to 2 cm) and also produced small dents on the aircraft nose cone after flying in smoky conditions at cloud base level on 23 September 2002.…”
Section: Discussionmentioning
confidence: 93%
“…4C), at least up to the aircraft operational height limitation of 4.5 km. Satellite retrievals of cloud top particle effective radius (20) suggested that the precipitation threshold of 14 m was exceeded at -22°C and -28°C, which correspond to H of 6600 and 7600 m for the smoky and pyro-clouds, respectively (Fig. 5).…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%
“…In the radiative transfer calculations we use the model of Rosenkranz and the model of Liebe for the absorption coefficient calculations: Rosenkranz (1998) for H 2 O, Rosenkranz (1993) for O 2 and Liebe et al (1993) for N 2 (Stähli et al, 2013). A tropospheric water vapour profile with an exponential decrease is included.…”
Section: Retrievalmentioning
confidence: 99%
“…This parameter indicates the mass of liquid water per unit volume of air and is usually expressed in g m −3 . Different authors have characterized the LWC for different kinds of clouds (Hess et al, 1998;Korolev et al, 2007;Rosenfeld and Lensky, 1998). Cirrus and fog present much lower water content than other kinds of clouds, with values around 0.03 and 0.06 g m −3 , respectively.…”
Section: Cloud Characterizationmentioning
confidence: 99%